Analisis pengaruh investasi, tenaga kerja dan indeks pembangunan manusia terhadap pertumbuhan ekonomi di Provinsi Jambi - Dede Maulana Putra; Parmadi Parmadi; Muhammad Safri (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
The purpose of this study (1) To Analyze Investment Development, Labor, Human Development Index and Economic Growth in Jambi Province (2) To Analyze the Effect of Investment, Labor, Human Development Index on Economic Growth in Jambi Province. In this study the data used are secondary data in the form of panel data, namely the data consists of two parts, namely: time series and cross section, time series data is annual data, namely 2005-2019, and cross sections are as many as 11 districts of the city. in Jambi Province. Obtained from government agencies and from internet sites that have been processed further .. Data processing is done using Microsoft Excel Software program and E-SPSS. 20. Based on the results of the study that simultaneously investment, labor, and the human development index have a significant effect on economic growth in Jambi Province in 2005-2019. Meanwhile, partially investment and human development index have a significant effect on economic growth in Jambi Province in 2005-2019.